Donor chimerism and bcr-abl gene status following non-myeloablative peripheral blood stem cell transplantation in chronic myeloid leukaemia patients in HUKM - Seman, Zainina; Leong, Chooi Fun; Hussin, Noor Hamidah; Othman, Ainoon; Cheong, Soon Keng (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2008)
Objective: This study was done to determine the relationship between donor chimerism and the presence of bcr-abl gene in chronic myeloid leukaemia (CML) patients post-transplantation. Methods: The study population consisted of all CML patients who had undergone non-myeloablative peripheral blood stem cell transplant in Hospital Universiti Kebangsaan Malaysia (HUKM) during the study period. All patients had their bone marrow aspiration done at diagnosis and day 30, 60, 100, 130, 160 and 190 post-transplantation. The samples were analysed for bcr-abl transcript as well as chimerism status. Results: A total of nine cases underwent non-myeloablative peripheral blood stem cell transplant. All patients were transplanted during the chronic phase. One patient was found to show mixed chimerism at day 30 post-transplant coinciding with bcr-abl transcript disappearance. Six patients showed that full donor chimerism correlated with bcr-abl transcript disappearance. In one patient, chronic myeloid leukaemia transformed into acute myeloid leukaemia. Another patient had a graft failure. Conclusion: This observational cohort study showed that full chimerism is required for disappearance of bcr-abl transcript but one case showed disappearance of bcr-abl transcript at day 30 while full chimerism was not achieved.